Handbook of Halophytes 2020
DOI: 10.1007/978-3-030-17854-3_78-1
|View full text |Cite
|
Sign up to set email alerts
|

Osmoprotectants and Nonenzymatic Antioxidants in Halophytes

Abstract: Salt tolerance is a complex phenomenon leading to ionic imbalance, osmotic stress, and excessive generation of reactive oxygen species (ROS). Halophytes developed a range of adaptations to tolerate disturbances in their redox homeostasis caused by high salinity alone or by its combination with other stresses. Osmoprotectants are universal molecules whose chemical structure allows them for making efficient osmotic adjustments and exerting antioxidant activity. Combining these two abilities, they become effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
(199 reference statements)
0
2
0
Order By: Relevance
“…Some studies have indicated that antioxidant natural products exhibit pigmentation-delaying properties by scavenging oxygen and nitrogen species as well as reducing intermediate quinone derivatives that play roles in the oxidative polymerization steps of melanogenesis ( Nahhas et al, 2019 ; Xing et al, 2022 ). In this context, halophytes are known for their diverse and abundant content of antioxidants ( Surówka and Hura, 2020 ). Moreover, UV radiation was suggested to increase the α-MSH-mediated tyrosinase production using free radicals whose levels were elevated during prolonged exposure to UV ( Nahhas et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have indicated that antioxidant natural products exhibit pigmentation-delaying properties by scavenging oxygen and nitrogen species as well as reducing intermediate quinone derivatives that play roles in the oxidative polymerization steps of melanogenesis ( Nahhas et al, 2019 ; Xing et al, 2022 ). In this context, halophytes are known for their diverse and abundant content of antioxidants ( Surówka and Hura, 2020 ). Moreover, UV radiation was suggested to increase the α-MSH-mediated tyrosinase production using free radicals whose levels were elevated during prolonged exposure to UV ( Nahhas et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the majority of halophytes are thought to represent salt accumulators, but even for these species, the ion concentration in the mesophyll tissues of photosynthetically active organs can be diminished by means of salt secretion to the leaf surface (recretohalophytes), an increase in tissue water content (succulent halophytes) and the accumulation of salts in older leaves [ 4 ]. Salt-accumulating halophytes use a cellular compartmentation strategy, accumulating salts in vacuoles, further solving a problem of proper osmotic adjustment [ 15 ]. The control of electrolytical activity in plant tissues due to salinity has been much less often considered, but it seems that coastal species from salt-affected habitats show different strategies, regulating leaf tissue electrical conductivity (EC) by changes in either K + or Na + concentration, but some species relatively tightly control the EC level by concomitant changes in both K + and Na + concentration [ 16 ].…”
Section: Introductionmentioning
confidence: 99%